Battery, electric device, and vehicle

CN122992133APending Publication Date: 2026-10-27BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610245174.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本申请提供一种电池、用电设备和车辆,以解决相关技术中电池在充放电过程中,正、负极活性材料发生体积膨胀和收缩导致正极极片和负极极片分别与固态电解质层之间的固-固界面产生微观间隙或接触不良的问题

Benefits of technology

本申请实施例所提供的电池包括正极极片和负极极片,正极极片包括正极集流体以及设置于正极集流体上的正极活性材料层,正极活性材料层包括正极活性材料,正极活性材料的化学式为Li1+xNiyCozMn1-x-y-zO2;其中x≥0.1,0≤y≤0.2,0≤z≤0.2,负极极片包括负极集流体以及设置于负极集流体上的负极活性材料层,负极活性材料层包括负极活性材料,负极活性材料包括钛酸锂。在本申请中,该正极活性材料为锂化学计量超过1的富锂锰基正极活性材料,因此在该正极活性材料的锂层占据有绝大部分的锂离子的情况下,过渡金属层还占据了部分锂离子,这使得在充电(脱锂反应)过程中,锂层的锂离子脱出后,过渡金属层中的锂离子能够发生层内或层间迁移,并填入至锂层因脱出锂离子而产生的空位中,该脱锂反应主要表现为锂离子在正极活性材料晶体内部位点之间的可逆重排与再分布,减小了正极活性材料晶格参数的波动,从而降低了正极活性材料在整个充放电循环中体积膨胀与收缩的程度,有助于确保正极极片与固态电解质层之间的固-固界面保持紧密、稳定的物理接触;同时,由于负极活性材料钛酸锂的晶体框架具有大量可容纳锂离子的晶体空位,在充放电过程中,锂离子仅在晶体空位之间进行可逆的嵌入和脱出,整个过程不涉及晶体骨架的断裂、重建或明显的晶格畸变,降低了负极活性材料层在整个充放电循环中体积膨胀与收缩的程度,从而从整体上降低了正极极片和负极极片分别与固态电解质层之间的固-固界面阻抗,提升了锂离子的传输效率和稳定性,从而延长了固态电池的循环寿命,减缓了电池容量的衰减速度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides a battery, a power utilization device and a vehicle, the battery comprising a positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode active material layer arranged on the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material, the chemical formula of the positive electrode active material being Li 1+x Ni y Co z Mn 1‑x‑y‑z O2; wherein x is greater than or equal to 0.1, y is greater than or equal to 0 and less than or equal to 0.2, and z is greater than or equal to 0 and less than or equal to 0.2, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising lithium titanate, so that the solid-solid interface impedance between the positive electrode sheet and the negative electrode sheet and the solid-state electrolyte layer is reduced as a whole, the transmission efficiency and stability of lithium ions are improved, the volume change rate of the battery is reduced, and the cycle life of the solid-state battery is prolonged, and the capacity decay rate of the battery is slowed down.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a battery, electrical equipment, and vehicle. Background Technology

[0002] Batteries include solid-state batteries, which consist of a positive electrode, a solid electrolyte layer, and a negative electrode stacked sequentially, and are characterized by high volumetric energy density. During the charging and discharging process of a solid-state battery, the active materials of the positive and negative electrodes undergo reactions involving the insertion and extraction of active ions, respectively, to achieve the storage and release of electrical energy.

[0003] However, the intercalation / extraction of active ions causes repeated volume expansion and contraction of the positive and negative active materials, resulting in microscopic gaps or poor contact at the solid-solid interface between the positive or negative electrode and the solid electrolyte layer. This hinders the efficient transport of active ions and causes uneven local current distribution, leading to an increased rate of change in battery volume and ultimately accelerating the degradation of battery capacity and cycle life.

[0004] In related technologies, mechanical pressure devices are used to suppress the impact of volume changes on the interface. However, such mechanical pressure devices not only increase the complexity and weight of the battery system, but also cannot fundamentally solve the problem of interface contact failure caused by the excessive volume change rate of the active material itself. Summary of the Invention

[0005] This application provides a battery, electrical device, and vehicle to solve the problem in the related art where, during the charging and discharging process of a battery, the volume expansion and contraction of the positive and negative electrode active materials leads to microscopic gaps or poor contact at the solid-solid interface between the positive and negative electrode sheets and the solid electrolyte layer.

[0006] To solve the above problems, this application provides the following technical solution: This application discloses a battery including a positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive active material layer disposed on the positive current collector, the positive active material layer comprising a positive active material having the chemical formula Li. 1+x Ni y Co z Mn 1-x-y-z O; where x≥0.1, 0≤y≤0.2, 0≤z≤0.2; the negative electrode includes a negative current collector and a negative active material layer disposed on the negative current collector, the negative active material layer includes a negative active material, the negative active material includes lithium titanate.

[0007] In some embodiments, 0.1 ≤ x ≤ 0.3; and / or, when the battery is charged and discharged at a rate of 0.1 C and an external static pressure of 2 to 5 MPa, the volume change rate of the battery is -0.01% to -2%.

[0008] In some embodiments, the battery further includes a solid electrolyte layer, the positive electrode and the negative electrode are respectively disposed on both sides of the solid electrolyte layer, and the solid electrolyte layer includes a solid electrolyte; And / or, at least one of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer further includes a modified binder, the modified binder including rubber and vulcanization initiator.

[0009] In some embodiments, the positive electrode active material layer comprises, by mass, 80-90 parts of the positive electrode active material and 0.5-2 parts of modified binder; And / or, in the negative electrode active material layer, by mass parts, it includes 85 to 95 parts of the negative electrode active material and 2 to 4 parts of modified binder; And / or, the solid electrolyte layer comprises, by mass, 92 to 96 parts of the solid electrolyte and 4 to 8 parts of the modified binder; And / or, the rubber includes at least one of natural rubber and synthetic rubber; And / or, the solid electrolyte includes at least one of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, and a polymer solid electrolyte; and / or, at least one of the positive electrode active material layer and the negative electrode active material layer further includes the solid electrolyte.

[0010] In some embodiments, the synthetic rubber includes at least one of nitrile rubber, polyisobutylene rubber, styrene-butadiene rubber, chloroprene rubber, polysulfide rubber, polyurethane rubber, and polyacrylate rubber; And / or, the vulcanization initiator includes a vulcanizing agent, which includes sulfur; And / or, the vulcanization initiator further includes an accelerator, the accelerator comprising at least one of 2-thiol-benzothiazole, dibenzothiazole disulfide, N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxadiethylene-2-benzothiazole sulfenamide, N,N'-dicyclohexyl-2-benzothiazole sulfenamide, tetramethylthiuram disulfide, tetramethylthiuram monosulfide, tetraethylthiuram disulfide, pentamethylthiuram hexasulfide, zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, zinc dimethyldithiocarbamate, and diphenylguanidine. And / or, the sulfidation initiator further includes fatty acids and metal oxides, wherein the fatty acids have 12 to 22 carbon atoms.

[0011] In some embodiments, the mass ratio of the vulcanizing agent, the metal oxide, the accelerator, and the fatty acid is (1.5~2.5):(1.5~2.5):(4.5~5.5):(0.5~1.5).

[0012] In some embodiments, the positive electrode active material is further doped with at least one of the following doping elements: W, Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, and Zr.

[0013] In some embodiments, the mass percentage of the dopant element is 0.01% to 0.2% based on the total mass of the positive electrode active material.

[0014] In some embodiments, the surface of the positive electrode active material is provided with a coating layer, the coating layer comprising one or more of Li2ZrO3, LiAlO2, AlF3 and MgO; and / or, the thickness of the coating layer is 2~20nm.

[0015] This application also proposes an electrical device including the aforementioned battery, wherein the battery serves as the power supply for the electrical device.

[0016] This application also proposes a vehicle including the aforementioned battery, which serves as a power source for the vehicle.

[0017] Compared with related technologies, the embodiments of this application have the following advantages: The battery provided in this application embodiment includes a positive electrode and a negative electrode. The positive electrode includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer includes a positive active material with the chemical formula Li. 1+x Ni y Co z Mn 1-x-y-zO2; where x≥0.1, 0≤y≤0.2, 0≤z≤0.2, the negative electrode includes a negative current collector and a negative active material layer disposed on the negative current collector, the negative active material layer includes a negative active material, the negative active material includes lithium titanate. In this application, the positive active material is a lithium-rich manganese-based positive active material with a lithium stoichiometry exceeding 1. Therefore, when the lithium layer of the positive active material occupies most of the lithium ions, the transition metal layer also occupies a portion of the lithium ions. This allows the lithium ions in the transition metal layer to migrate intralayer or interlayer after being removed from the lithium layer during the charging (delithiation reaction) process, and fill the vacancies created by the removal of lithium ions from the lithium layer. This delithiation reaction mainly manifests as the reversible rearrangement and redistribution of lithium ions between sites within the positive active material crystal, reducing the fluctuation of the lattice parameters of the positive active material, thereby reducing the degree of volume expansion and contraction of the positive active material during the entire charge-discharge cycle, which helps to ensure The solid-solid interface between the positive electrode and the solid electrolyte layer maintains a tight and stable physical contact. Meanwhile, because the crystal framework of the negative electrode active material lithium titanate has a large number of crystal vacancies that can accommodate lithium ions, during the charging and discharging process, lithium ions only undergo reversible insertion and extraction between crystal vacancies. The entire process does not involve the breakage, reconstruction, or significant lattice distortion of the crystal framework, reducing the degree of volume expansion and contraction of the negative electrode active material layer throughout the charging and discharging cycle. This reduces the solid-solid interface impedance between the positive and negative electrode sheets and the solid electrolyte layer, thereby improving the lithium ion transport efficiency and stability, extending the cycle life of the solid-state battery, and slowing down the rate of battery capacity decay. Detailed Implementation

[0018] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to specific embodiments.

[0019] In battery systems, batteries include solid-state batteries and liquid-state batteries. Solid-state batteries consist of a positive electrode, a solid electrolyte layer, and a negative electrode stacked sequentially, characterized by high volumetric energy density. Liquid-state batteries consist of a positive electrode, a separator, and a negative electrode stacked sequentially. During manufacturing, the positive electrode, separator, and negative electrode are stacked in sequence and wound into a bare cell using a winding process. Subsequently, an electrolyte is injected into the bare cell to obtain a liquid-state battery. Taking the positive electrode as an example, both solid-state and liquid-state batteries have a positive current collector and a layer of positive active material disposed on the current collector. The positive active material layer includes positive active material.

[0020] In both liquid and solid-state batteries, the positive electrode active material undergoes repeated electrochemical volume deformation during charging and discharging due to the insertion and extraction of active ions. This continuous volume change gradually damages the contact interface between the positive electrode and the electrolyte. In liquid batteries, the electrolyte's excellent fluidity and wettability allow it to dynamically fill the micro-gaps created by volume changes, thus minimizing the impact of volume changes on the transport efficiency of active ions within the battery. However, in solid-state batteries, the solid electrolyte layer lacks the self-regulating capability of electrolytes. Once the positive and negative electrode active materials undergo volume deformation, irreparable gaps will form at the solid-solid interfaces between the positive and negative electrodes and the solid electrolyte layer. This leads to interrupted ion transport channels, a sharp increase in interfacial impedance, uneven current distribution, and ultimately, rapid capacity decay and reduced cycle life.

[0021] Related technologies typically employ methods that apply enormous external static pressure, attempting to constrain the expansion of the electrode sheets and maintain tight contact at the solid-solid interface through mechanical force. This can be achieved by integrating mechanical pressure systems such as clamps, springs, or hydraulic devices within the battery module. However, this large and complex mechanical pressure system encroaches on the space and weight within the battery module, contradicting the original intention of high energy density in solid-state batteries. Furthermore, the continuous high-pressure environment poses stringent challenges to the battery module's packaging technology, safety, and long-term stability, while also increasing manufacturing costs and system complexity.

[0022] To address the issue of volume expansion and contraction of the positive active material in the positive electrode layer and the negative active material in the negative electrode layer during battery charging and discharging, this embodiment provides a battery comprising a positive electrode sheet and a negative electrode sheet. The positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer comprises a positive active material with the chemical formula Li. 1+x Ni y Co z Mn 1-x-y-z O2; where x≥0.1, 0≤y≤0.2, 0≤z≤0.2, the negative electrode sheet includes a negative current collector and a negative active material layer disposed on the negative current collector, the negative active material layer includes a negative active material, and the negative active material includes lithium titanate.

[0023] The atomic stacking of the positive electrode active material in this application embodiment is a "sandwich" structure, specifically including an oxygen ion layer, and lithium layers and transition metal layers alternately stacked between the oxygen ion layers. The transition metal layer is composed of transition metal ions. Since the lithium stoichiometry of the positive electrode active material exceeds 1 (x≥0.1), while the lithium layer of the positive electrode active material occupies most of the lithium ions, the transition metal layer also occupies a portion of the lithium ions. The lithium ions in the transition metal layer and the transition metal ions form an ordered or partially ordered arrangement.

[0024] During the charging (lithiation reaction), lithium ions are extracted from the lithium layer. Simultaneously, lithium ions in the transition metal layer can migrate intralayer or interlayer and fill the vacancies created by the extraction of lithium ions from the lithium layer. This process transforms the lithium ion extraction reaction from the extraction of lithium ions from the crystal lattice in related technologies into a reversible rearrangement of lithium ions between sites within the crystal. This lithium ion extraction reaction, dominated by reversible rearrangement of lithium ions, reduces the fluctuation of the lattice parameters of the positive electrode active material, thereby reducing the degree of volume expansion and contraction of the positive electrode active material throughout the charge-discharge cycle. This helps ensure that the solid-solid interface between the positive electrode and the solid electrolyte layer maintains a tight and stable physical contact, thereby reducing the solid-solid interface impedance between the positive electrode and the solid electrolyte layer, improving the lithium ion transport efficiency and stability, thus increasing the cycle life of the solid-state battery and slowing down the rate of battery capacity decay.

[0025] In some embodiments, 0.1 ≤ x ≤ 0.3. When x ≥ 0.1, it ensures that the transition metal layer occupies a sufficient amount of lithium ions to migrate and fill the vacancies generated by lithium delithiation in the lithium layer during the delithiation reaction, thereby reducing the fluctuation of the lattice parameters of the cathode active material and reducing the degree of volume change of the cathode active material throughout the charge-discharge cycle. When x does not exceed 0.3, it avoids the decrease in structural stability of the cathode active material caused by excessive lithium content. Controlling the stoichiometric number y of nickel between 0 and 0.2 aims to improve the reversible capacity and ionic conductivity of the cathode active material with an appropriate amount of nickel, while avoiding excessive nickel content from aggravating cation mixing and structural degradation. Controlling the stoichiometric number z of cobalt between 0 and 0.2 provides flexible space for adjusting the electronic conductivity and structural stability of the cathode active material.

[0026] In some embodiments, the positive electrode active material includes Li 1.05 Ni 0.1 Co 0.1 Mn 0.75 O2, Li 1.1 Ni 0.05 Mn 0.85 O2, Li 1.15 Ni 0.15 Co 0.10 Mn 0.60O2, Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, Li 1.3 Ni 0.2 Co 0.2 Mn 0.3 O2, Li 1.3 Mn 0.7 At least one of O2.

[0027] In some embodiments, the negative electrode sheet of the battery includes a negative current collector and a negative active material layer disposed on the negative current collector, wherein the negative active material layer includes a negative active material, and the negative active material includes lithium titanate.

[0028] From a structural perspective, lithium titanate (Li4Ti5O) 12 The solid-state battery has a spinel-type structure, with a stable and rigid three-dimensional crystal framework composed of titanium and oxygen ions, and a large number of crystal vacancies that can accommodate lithium ions. During charging and discharging, lithium ions only undergo reversible insertion and extraction between crystal vacancies. The entire process does not involve the breakage, reconstruction, or significant lattice distortion of the crystal framework. This reduces the degree of volume expansion and contraction of the negative electrode active material layer throughout the charge-discharge cycle, thereby helping to ensure a tight and stable physical contact between the solid-solid interface of the negative electrode active material layer and the solid electrolyte layer. This reduces the solid-solid interface impedance between the negative electrode active material layer and the solid electrolyte layer, improves the lithium ion transport efficiency and stability, and thus improves the cycle life of the solid-state battery and slows down the rate of battery capacity decay.

[0029] Therefore, in this application, the battery includes a positive electrode and a negative electrode. The positive electrode includes a positive active material layer, and the positive active material layer includes a positive active material with the chemical formula Li. 1+x Ni y Co z Mn 1-x-y-z O2, the negative electrode sheet includes a negative active material layer, which contains a negative active material, namely lithium titanate. During charging, lithium ions from the lithium layer in the positive active material are extracted and pass through the solid electrolyte layer, embedding into the crystal vacancies of lithium titanate in the negative active material layer. During discharging, lithium ions are extracted from the crystal vacancies of lithium titanate in the negative electrode and return to the positive active material layer through the solid electrolyte layer. Furthermore, during charging and discharging, on the one hand, lithium ions in the transition metal layer of the positive active material can undergo interlayer migration and fill the vacancies created by lithium ion extraction in the lithium layer; on the other hand, lithium ions can reversibly insert and extract only between the crystal vacancies of lithium titanate. The entire process does not involve the breakage, reconstruction, or significant lattice distortion of the lithium titanate crystal framework. Therefore, by selecting Li... 1+xNi y Co z Mn 1-x-y-z Using O2 as the positive electrode active material and lithium titanate as the negative electrode active material reduces the degree of volume expansion and contraction of the positive and negative electrode active material layers throughout the charge-discharge cycle. This solves the problem of gaps, poor contact, or even complete detachment at the solid-solid interface between the positive and negative electrode sheets and the solid electrolyte layer caused by repeated volume changes of the positive and negative electrode active materials. It also reduces the solid-solid interface impedance between the positive and negative electrode sheets and the solid electrolyte layer, improving lithium-ion transport efficiency and stability, thereby increasing the cycle life of the solid-state battery and slowing down the rate of battery capacity decay. Testing showed that using Li... 1+ x Ni y Co z Mn 1-x-y-z Batteries using O2 as the positive electrode active material and lithium titanate as the negative electrode active material undergo charge-discharge cycles at a rate of 0.1 C and an external static pressure of 2-5 MPa. The overall volume change rate is between -0.01% and -0.2%, which helps to ensure the battery's high capacity and cycle life.

[0030] In some embodiments, when the battery is a liquid battery, the battery further includes an electrolyte and a separator. The separator is disposed between the positive electrode and the negative electrode. The electrolyte wets the surfaces of the positive electrode, the separator, and the negative electrode. The electrolyte includes an electrolyte salt and a solvent. The separator, through physical isolation, can prevent internal short circuits caused by direct contact between the positive and negative electrodes. At the same time, the microporous structure in the separator can ensure the migration of lithium ions in the electrolyte and maintain the stable conduct of the electrochemical reaction.

[0031] In some embodiments, the electrolyte salt is a lithium salt, including at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium hexafluoroaluminate, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium dioxoyl borate, lithium difluorophosphate, and lithium nitrate; the solvent includes cyclic ester solvents and chain ester solvents. In some embodiments, the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, butenyl carbonate, fluoroethylene carbonate, and γ-butyrolactone; the chain ester solvent includes at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, and diphenyl carbonate. In some embodiments, the solvent includes ethylene carbonate, propylene carbonate, and methyl ethyl carbonate.

[0032] In some embodiments, when the battery is a solid-state battery, the battery further includes a solid electrolyte layer, with a positive electrode and a negative electrode respectively disposed on both sides of the solid electrolyte layer. The solid electrolyte layer includes a solid electrolyte, and at least one of the positive electrode active material layer, the negative electrode active material layer and the solid electrolyte layer further includes a modified binder, which includes rubber and a vulcanization initiator.

[0033] In the positive electrode active material layer, the modified binder coats the surface of the positive electrode active material particles or fills the spaces between them; and in the negative electrode active material layer, the modified binder coats the surface of the negative electrode active material particles or fills the spaces between them. By triggering the vulcanization initiator and the rubber to undergo a thermal crosslinking and curing reaction, a stable three-dimensional elastic network is formed in the positive electrode active material layer and the negative electrode active material layer, respectively. This three-dimensional elastic network structure can compensate for and buffer the micro-stress generated by the volume changes of the positive and negative electrode active materials during charging and discharging, thereby helping to maintain close contact between the solid-solid interface of the positive and negative electrode sheets and the solid electrolyte layer, respectively.

[0034] In some embodiments, the solid electrolyte layer includes a solid electrolyte and a modified binder. The modified binder is coated on the surface of the solid electrolyte particles or filled between the solid electrolyte particles. By triggering a thermal crosslinking and curing reaction between the vulcanization initiator and the rubber, a stable three-dimensional elastic network is formed in the solid electrolyte layer. This three-dimensional elastic network can buffer and absorb the stress on the solid electrolyte layer caused by the volume expansion and contraction of the positive electrode active material layer and the negative electrode active material layer, thereby helping to ensure that the solid-solid interface between the positive and negative electrode sheets and the solid electrolyte layer maintains a tight and stable physical contact.

[0035] This modified binder comprises rubber and a vulcanization initiator. The vulcanization initiator initiates a thermal cross-linking and curing reaction in the rubber, generating a three-dimensional elastic network structure. During charging and discharging, when the positive and negative electrode active materials expand or contract due to lithium insertion / extraction, these three-dimensional elastic network structures can absorb and disperse micro-stress through their reversible deformation, preventing stress accumulation that could lead to debonding or cracking at the solid-solid interface. Simultaneously, this three-dimensional elastic network structure fills the original micro-gaps between the positive electrode active material layer and the solid electrolyte particle layer, and between the negative electrode active material layer and the solid electrolyte layer, improving the continuity of the lithium-ion transport channels.

[0036] In some embodiments, the solid electrolyte layer includes a solid electrolyte and a modified binder, the positive electrode active material layer includes a positive electrode active material and a modified binder, and the negative electrode active material layer includes a negative electrode active material and a modified binder.

[0037] In some embodiments, the positive electrode active material layer comprises, by mass, 80-90 parts of positive electrode active material and 0.5-2 parts of modified binder.

[0038] In the positive electrode active material layer, 80 to 90 parts of positive electrode active material ensure that the positive electrode active material layer has a high energy density; 0.5 to 2 parts of modified binder provide sufficient polymer matrix for constructing a three-dimensional elastic network, which is conducive to forming a stable three-dimensional elastic network between positive electrode active material particles, while avoiding excessive amount leading to a significant decrease in the ionic conductivity of the positive electrode active material layer.

[0039] In some embodiments, the positive electrode active material layer comprises, by weight, 80 parts of positive electrode active material and 0.55 parts of modified binder; or, the positive electrode active material layer comprises, by weight, 85 parts of positive electrode active material and 1 part of modified binder; or, the positive electrode active material layer comprises, by weight, 90 parts of positive electrode active material and 2 parts of modified binder.

[0040] In some embodiments, the negative electrode active material layer comprises 85 to 95 parts by mass of negative electrode active material and 2 to 4 parts by mass of modified binder. The high mass proportion of negative electrode active material ensures battery capacity, while an appropriate amount of modified binder can form a stable three-dimensional elastic network between the negative electrode active material particles and enhance the overall toughness of the negative electrode active material layer without significantly increasing impedance.

[0041] In some embodiments, the negative electrode active material layer comprises, by weight, 85 parts of negative electrode active material and 2 parts of modified binder; or, by weight, the negative electrode active material layer comprises, by weight, 90 parts of negative electrode active material and 3 parts of modified binder; or, by weight, the negative electrode active material layer comprises, by weight, 95 parts of negative electrode active material and 4 parts of modified binder.

[0042] In some embodiments, the solid electrolyte layer comprises 92 to 96 parts by mass of solid electrolyte and 4 to 8 parts by mass of modified binder. The high mass proportion of solid electrolyte ensures the active ion conduction function of the solid electrolyte layer, while an appropriate amount of modified binder can form a three-dimensional elastic network between the solid electrolyte particles. This three-dimensional elastic network can effectively buffer the volume change stress from the positive and negative electrodes.

[0043] In some embodiments, the solid electrolyte layer comprises, by weight, 92 parts solid electrolyte and 4 parts modified binder; or, by weight, 94 parts solid electrolyte and 6 parts modified binder; or, by weight, 96 parts solid electrolyte and 8 parts modified binder.

[0044] In some embodiments, the positive electrode active material layer and the negative electrode active material layer further include conductive agents, which may be acetylene black, carbon fiber, carbon nanotubes, Ketjen black, artificial graphite, natural graphite, hard carbon, soft carbon, carbon black, graphene, etc.

[0045] In some embodiments, the rubber includes at least one of natural rubber and synthetic rubber. Synthetic rubber includes at least one of nitrile rubber (NBR), polyisobutylene rubber (PIB), styrene-butadiene rubber (SBR), chloroprene rubber (CR), polysulfide rubber (T), polyurethane rubber (PU), and polyacrylate rubber (ACM). In some embodiments, the rubber comprises nitrile rubber and polyisobutylene rubber in a mass ratio of (3-5):7.

[0046] The vulcanization initiator includes a vulcanizing agent, which includes sulfur; the vulcanization initiator also includes an accelerator, which includes at least one of 2-thiol-benzothiazole, dibenzothiazole disulfide, N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxodiethylene-2-benzothiazole sulfenamide, N,N'-dicyclohexyl-2-benzothiazole sulfenamide, tetramethylthiuram disulfide, tetramethylthiuram monosulfide, tetraethylthiuram disulfide, pentamethylthiuram hexasulfide, zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, zinc dimethyldithiocarbamate, and diphenylguanidine.

[0047] The sulfidation initiator also includes fatty acids and metal oxides, wherein the fatty acids have 12 to 22 carbon atoms. The fatty acids include at least one of stearic acid, lauric acid, and oleic acid, and the metal oxides include at least one of aluminum oxide, lead oxide, and magnesium oxide.

[0048] In the vulcanization initiator system, sulfur provides sulfur atoms to connect rubber molecular chains to form a three-dimensional elastic network structure; metal oxides are activation centers that can react with fatty acids to generate active complexes that promote sulfur activation, thereby effectively transporting insoluble metal oxides to the reaction interface and adjusting the polarity of the rubber phase to optimize the dispersion of each component; there are many types of accelerators, whose role is to reduce the activation energy of the thermal crosslinking and curing reaction of sulfur, improve crosslinking efficiency and selectivity, and determine the crosslinking initiation temperature and rate. Different accelerators can achieve flexible triggering from room temperature to high temperature.

[0049] In some embodiments, the mass ratio of vulcanizing agent, metal oxide, accelerator and fatty acid is (1.5~2.5):(1.5~2.5):(4.5~5.5):(0.5~1.5), wherein the amount of sulfur and metal oxide is roughly equal to ensure sufficient active reaction sites; the accelerator accounts for the largest proportion to improve the overall crosslinking kinetics; and the fatty acid is the least amount, its role being to react with the metal oxide to generate active complexes, which ultimately helps to ensure the formation of a three-dimensional elastic network structure with excellent mechanical properties.

[0050] To trigger the thermal crosslinking and curing reaction, during the preparation of the solid-state battery, the positive electrode, solid electrolyte layer, and negative electrode are stacked and assembled to obtain an electrode assembly. The electrode assembly is then placed in a lamination mold and subjected to isostatic pressing. During isostatic pressing, a pressure of 420~480 MPa is applied to the electrode assembly for 20~40 minutes. Subsequently, a pressure of 420~480 MPa is continuously applied, and the temperature is raised to 150~180℃ to trigger the thermal crosslinking and curing reaction of the modified binder for 8~9 hours, ultimately yielding the solid-state battery.

[0051] In some embodiments, the positive electrode active material is further doped with at least one of the following doping elements: W, Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, and Zr.

[0052] By doping the above-mentioned doping elements during the sintering stage of the positive electrode active material, these doping elements improve the performance of the positive electrode active material by occupying the crystal lattice or grain boundaries. Among them, high-valence elements such as Al, Mg, Ti, Zr and Nb can stabilize the oxygen ion framework of the positive electrode active material, inhibit oxygen release, reduce phase transition, and thus improve the structural stability of the positive electrode active material particles. Doping with elements such as Na, K, Cu, Ni and Co can reduce the internal resistance of the positive electrode active material, thereby improving the rate performance of the battery. Elements such as B, S, Si, N, F, C and Br can form a stable coating layer or passivation layer on the surface of the positive electrode active material particles to protect the interface. Elements such as W, V, Cr, Zn, Ca, Sr and Pb have the functions of stabilizing the structure and modifying the surface.

[0053] In some embodiments, based on the total mass of the positive electrode active material, the mass percentage of the doping element is 0.01% to 0.2%. An appropriate mass of doping element is beneficial for it to play an effective role in the lattice or surface, while also preventing the problem of battery performance being affected by the occupation of active lithium sites due to excessive doping.

[0054] In some embodiments, a coating layer is provided on the surface of the positive electrode active material, the coating layer including one or more of Li2ZrO3, LiAlO2, AlF3, and MgO. In the preparation process, zirconium-containing compounds such as zirconium butoxide, zirconium oxychloride, and zirconium isopropoxide are mixed with the positive electrode active material and sintered to form a Li2ZrO3 coating layer on the surface of the positive electrode active material; or aluminum-containing compounds such as aluminum nitrate and aluminum oxide are mixed with the positive electrode active material and sintered to form a LiAlO2 coating layer on the surface of the positive electrode active material; or aluminum fluoride, ammonium fluoride, lithium fluoride, etc. are used as fluorine sources, and aluminum nitrate or aluminum oxide is used as aluminum sources, so that the fluorine source and aluminum source are mixed with the positive electrode active material and sintered to form an AlF3 coating layer on the surface of the positive electrode active material; or magnesium-containing compounds such as magnesium acetate, magnesium nitrate, and magnesium hydroxide are mixed with the positive electrode active material and sintered to form a MgO coating layer on the surface of the positive electrode active material. These coatings have excellent chemical inertness and can form a dense and stable physical barrier on the surface of the positive electrode active material, effectively reducing the direct contact between the transition metal ions of the positive electrode active material and the solid electrolyte layer, thereby suppressing the side reactions between the positive electrode active material and the solid electrolyte layer and slowing down the capacity decay during cycling.

[0055] In some embodiments, the thickness of the coating layer is 2 to 20 nm. This thickness range allows the coating layer to effectively isolate the positive electrode active material from the side reaction of the solid electrolyte and suppress the dissolution of transition metals while maintaining a relatively fast lithium-ion transport rate. This improves the stability and cycle life of the positive electrode active material without significantly sacrificing its rate performance.

[0056] In some embodiments, the positive electrode active material layer further includes a solid electrolyte, which, by distributing the solid electrolyte in the positive electrode active material layer, constructs a relatively efficient ion transport channel in the positive electrode active material layer; in some embodiments, the negative electrode active material layer further includes a solid electrolyte, which, by distributing the solid electrolyte in the negative electrode active material layer, constructs a relatively efficient ion transport channel in the negative electrode active material layer; and the solid electrolyte layer disposed between the positive electrode and the negative electrode serves as an ion transport bridge throughout the solid-state battery, working in synergy with the ion transport channels inside the positive and negative electrodes to ensure that lithium ions can quickly and stably complete migration and cycling throughout the entire battery during charging and discharging.

[0057] Solid electrolytes include at least one of sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes, and polymer solid electrolytes.

[0058] Among them, oxide solid electrolytes include Li 6.4 La3Zr 1.4 Ta 0.6 O 12 Li7La3Zr2O12 or Li7La3Zr2O 12 It has superior chemical and electrochemical stability and high safety; at the same time, oxide solid electrolytes have high stability in air and are easy to process.

[0059] Sulfide solid electrolytes, such as Li3PS4 or Li7P3S 11 Sulfide solid electrolytes have high room temperature ionic conductivity.

[0060] Halogen solid electrolytes, such as Li6PS5Cl, Li3OCl, Li3OBr, or Li3OF, where Li6PS5Cl is made by introducing chloride ions into the lattice of Li3PS4, can optimize the transport path of lithium ions, thereby achieving high room temperature ionic conductivity.

[0061] Polymer solid electrolytes consist of a polymer matrix and a lithium salt. The flexible polymer chains can closely adhere to the electrode active material particles, buffering the volume changes of the electrode active material during charging and discharging. The lithium salt provides free lithium ions to achieve ion conduction, which helps to improve the cycle life of the battery.

[0062] The polymer matrix is ​​selected from at least one of polyether, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, and polycarbonate, and the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, and lithium perchlorate. In some embodiments, the polymer solid electrolyte includes at least one of polyethylene oxide-lithium bis(trifluoromethanesulfonyl)imide (PEO-LiTFSI), polyacrylonitrile-lithium perchlorate (PAN-LiClO4), polymethyl methacrylate-lithium bis(trifluoromethanesulfonyl)imide (PMMA-LiTFSI), polyvinylidene fluoride-lithium hexafluorophosphate (PVDF-LiPF6), or polycarbonate-lithium bis(trifluoromethanesulfonyl)imide (PPC-LiTFSI).

[0063] In some embodiments, this application also provides an electrical device including a battery, which serves as a power supply for the device. It should be noted that the battery disclosed in this embodiment has the same structure as the battery in the above embodiments, and its beneficial effects are similar. Therefore, it will not be repeated here; relevant details can be found in the description of the battery embodiments.

[0064] In some embodiments, the electrical device may further include an energy storage cabinet, a mobile phone, a tablet, a laptop, an electric toy, a ship, a spacecraft, etc. The electric toy may include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., while the spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.

[0065] In some embodiments, a vehicle is also provided, the vehicle including a battery that serves as a power source for the vehicle, the vehicle being, but not limited to, an electric vehicle, a hybrid electric vehicle, a range-extended electric vehicle, a fuel cell vehicle, an electric motorcycle, and an electric bicycle.

[0066] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the present application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. Unless otherwise specified, the reagents and instruments used in the embodiments and comparative examples are all commercially available, and the experimental operations are performed in accordance with the product instructions and standard experimental procedures.

[0067] Example 1 (1) Preparation of positive electrode sheet According to the mass fractions, 85 parts of positive electrode active material, 15 parts of Li6PS5Cl, 1 part of SuperP, 1 part of binder, and 0.6 parts of butyl butyrate (solvent) were mixed and stirred under vacuum for 60 minutes to form a uniform positive electrode slurry. Subsequently, the positive electrode slurry was coated onto an aluminum foil current collector to a thickness of 150 μm. Drying was then continued at 60°C for 30 minutes to completely remove the solvent, thus drying the positive electrode slurry on the aluminum foil current collector into a positive electrode active material layer, yielding the positive electrode sheet. The positive electrode active material is Li6PS5Cl. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2, the binder is nitrile rubber.

[0068] (2) Preparation of negative electrode sheet By weight, 90 parts of negative electrode active material, 10 parts of Li6PS5Cl, 2 parts of SuperP, 3 parts of binder, and 0.6 parts of butyl butyrate (solvent) were mixed and stirred under vacuum for 60 minutes to form a uniform negative electrode slurry. The negative electrode slurry was then coated onto a copper foil current collector to a thickness of 50 μm. Drying was continued at 60°C for 30 minutes to completely remove the solvent, thus drying the negative electrode slurry on the copper foil current collector into a negative electrode active material layer, yielding the negative electrode sheet. The negative electrode active material was lithium titanate (Li4Ti5O). 12 .

[0069] (3) Preparation of solid electrolyte layer By mass, 95 parts Li6PS5Cl, 5 parts binder, and 100 parts butyl butyrate (solvent) are mixed and stirred to form a uniform electrolyte slurry. The electrolyte slurry is then coated onto the positive electrode and the negative electrode, with a coating thickness of 150 μm on both electrodes. The mixture is then dried at 60 °C for 30 min to form a first sub-solid electrolyte layer on the surface of the positive electrode and a second solid electrolyte layer on the surface of the negative electrode. During battery assembly, the first and second sub-solid electrolyte layers are bonded together to form a solid electrolyte layer.

[0070] (4) Battery assembly and curing The electrode assembly is obtained by stacking and assembling the positive electrode, the first sub-solid electrolyte layer, the second sub-solid electrolyte layer, and the negative electrode in that order. The electrode assembly is then placed in a lamination mold and subjected to isostatic pressing. During the isostatic pressing, a pressure of 450 MPa is applied to the electrode assembly for 30 minutes. Subsequently, a pressure of 450 MPa is continuously applied, and the temperature is raised to 150°C for thermal crosslinking and curing reaction for 8 hours, ultimately producing an all-solid-state battery pouch.

[0071] Example 2 The difference from Example 1 is that the positive electrode active material is adjusted in step (1).

[0072] Example 3 The difference from Example 1 is that a step of preparing a modified adhesive is added before step (1). The preparation of the modified adhesive includes: weighing 0.5 parts of nitrile rubber and polyisobutylene with a mass ratio of 3:7, 9.5 parts of butyl butyrate (solvent), and 0.05 parts of vulcanization initiator, which includes sulfur, zinc oxide, mercaptobenzothiazole and stearic acid with a mass ratio of 2:2:5:1; placing the above materials in a planetary mixer and stirring at 800 rpm for 30 min to obtain the modified adhesive, and replacing the nitrile rubber in steps (1), (2) and (3) of Example 1 with this modified adhesive.

[0073] Example 4 The difference from Example 3 is that the positive electrode active material in step (1) was adjusted.

[0074] Example 5 The difference from Example 3 is that the type of rubber, the mass fraction of rubber, the mass fraction of vulcanization initiator, and the mass ratio of sulfur, zinc oxide, mercaptobenzothiazole, and stearic acid in the vulcanization initiator were adjusted in the step of preparing the modified binder.

[0075] Comparative Example 1 The difference from Example 1 is that the positive electrode active material in step (1) and the negative electrode active material in step (2) were adjusted.

[0076] Comparative Example 2 The difference from Example 3 is that the positive electrode active material in step (1) and the negative electrode active material in step (2) were adjusted.

[0077] The relevant parameters of the batteries prepared by the examples and comparative examples are shown in Tables 1 and 2.

[0078] Table 1

[0079] Table 2

[0080] The all-solid-state battery pouches from the above embodiments and comparative examples were placed in a test fixture capable of applying and maintaining a constant external pressure of 2 MPa at 25°C. Constant current charging tests were conducted at a rate of 0.1C within a voltage range of 1.0–3.0 V. The volume change rate of the all-solid-state battery pouches at each real-time voltage was measured using an in-situ battery expansion tester. The test results are shown in Table 3. Subsequently, constant current charge-discharge cycle tests were conducted at a rate of 0.5C within a voltage range of 1.0–3.0 V under a pressure of 2 MPa. The capacity retention rate of the all-solid-state battery pouches at different cycle numbers was recorded. The test results are shown in Table 4.

[0081] Table 3

[0082] Table 4

[0083] Compared with Comparative Examples 1 and 2, the test data in Tables 3 and 4 show that the volume change rate of the batteries prepared in Examples 1-5 of this application is significantly reduced throughout the charge-discharge process. In particular, when charged to 3.0V, the volume change rate of the comparative example batteries exceeds 4%, while the volume change of Examples 1-5 is effectively suppressed to between -0.01% and -1.15%. This demonstrates that the lithium-rich manganese-based cathode active material (Li...) of this application... 1+x Ni y Co z Mn 1-x-y-z O2, where x≥0.1, 0≤y≤0.2, 0≤z≤0.2), and paired with strain-free negative electrode active material lithium titanate Li4Ti5O 12 This reduces the volume change rate of solid-state batteries.

[0084] After 300 cycles at an external pressure of 2 MPa and a rate of 0.5C, the battery capacity retention rates of Examples 1-5 remained as high as 81.5% to 85.8%, which is superior to the comparative batteries (which showed severe capacity decay within 50 cycles). This confirms that the strategy of suppressing volumetric strain through the intrinsic structural design of the positive and negative electrode active materials in this application can solve the problems of interface failure and capacity decay caused by repeated expansion and contraction of electrodes in solid-state batteries. Furthermore, when the positive electrode material system of this application is combined with the sulfurized modified binder (as in Examples 3-5), a three-dimensional elastic network is constructed inside the electrode and electrolyte layers. This three-dimensional elastic network not only further buffers the minute volumetric stress but also optimizes the ion transport channels.

[0085] In summary, this application improves the integrity of the solid-solid interface in solid-state batteries, enhances ion transport efficiency and cycle stability, thereby achieving a synergistic improvement in energy density and cycle life of solid-state batteries without relying on complex external mechanical pressure systems.

[0086] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.

[0087] The present application provides a detailed description of a battery, electrical device, and vehicle. Specific examples have been used to illustrate the principles and implementation methods of the present application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present application. At the same time, those skilled in the art will recognize that there will be changes in the specific implementation methods and application scope based on the ideas of the present application. Therefore, the content of this specification should not be construed as a limitation of the present application.

Claims

1. A battery, characterized in that, The electrode includes a positive electrode and a negative electrode. The positive electrode includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer includes a positive active material with the chemical formula Li. 1+x Ni y Co z Mn 1-x-y-z O2, where x≥0.1, 0≤y≤0.2, 0≤z≤0.2; The negative electrode sheet includes a negative current collector and a negative active material layer disposed on the negative current collector. The negative active material layer includes a negative active material, and the negative active material includes lithium titanate.

2. The battery according to claim 1, characterized in that, 0.1≤x≤0.3; And / or, when the battery is charged and discharged at a rate of 0.1 C and an external static pressure of 2 to 5 MPa, the volume change rate of the battery is -0.01% to -2%.

3. The battery according to claim 1 or 2, characterized in that, It also includes a solid electrolyte layer, wherein the positive electrode and the negative electrode are respectively disposed on both sides of the solid electrolyte layer, and the solid electrolyte layer includes a solid electrolyte; And / or, at least one of the positive electrode active material layer, the positive electrode active material layer and the solid electrolyte layer further includes a modified binder, the modified binder including rubber and vulcanization initiator.

4. The battery according to claim 3, characterized in that, The positive electrode active material layer comprises, by mass parts, 80-90 parts of the positive electrode active material and 0.5-2 parts of modified binder; And / or, in the negative electrode active material layer, by mass parts, it includes 85 to 95 parts of the negative electrode active material and 2 to 4 parts of modified binder; And / or, the solid electrolyte layer comprises, by mass, 92 to 96 parts of the solid electrolyte and 4 to 8 parts of the modified binder; And / or, the rubber includes at least one of natural rubber and synthetic rubber; And / or, the solid electrolyte includes at least one of sulfide solid electrolyte, oxide solid electrolyte, halide solid electrolyte and polymer solid electrolyte; And / or, at least one of the positive electrode active material layer and the negative electrode active material layer further includes the solid electrolyte.

5. The battery according to claim 4, characterized in that, The synthetic rubber includes at least one of nitrile rubber, polyisobutylene rubber, styrene-butadiene rubber, chloroprene rubber, polysulfide rubber, polyurethane rubber, and polyacrylate rubber; And / or, the vulcanization initiator includes a vulcanizing agent, which includes sulfur; And / or, the vulcanization initiator further includes an accelerator, the accelerator comprising at least one of 2-thiol-benzothiazole, dibenzothiazole disulfide, N-cyclohexyl-2-benzothiazole sulfenamide, N-tert-butyl-2-benzothiazole sulfenamide, N-oxadiethylene-2-benzothiazole sulfenamide, N,N'-dicyclohexyl-2-benzothiazole sulfenamide, tetramethylthiuram disulfide, tetramethylthiuram monosulfide, tetraethylthiuram disulfide, pentamethylthiuram hexasulfide, zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, zinc dimethyldithiocarbamate, and diphenylguanidine. And / or, the sulfidation initiator further includes fatty acids and metal oxides, wherein the fatty acids have 12 to 22 carbon atoms.

6. The battery according to claim 5, characterized in that, The mass ratio of the vulcanizing agent, the metal oxide, the accelerator, and the fatty acid is (1.5~2.5):(1.5~2.5):(4.5~5.5):(0.5~1.5).

7. The battery according to any one of claims 1 to 6, characterized in that, The positive electrode active material is also doped with at least one of the following doping elements: W, Al, Na, K, Mg, Cu, Mn, Cr, Zn, Pb, Ca, Co, Ni, Sr, Nb, V, Ti, B, S, Si, N, F, Cl, Br, and Zr.

8. The battery according to claim 7, characterized in that, Based on the total mass of the positive electrode active material, the mass percentage of the doping element is 0.01% to 0.2%.

9. The battery according to any one of claims 1 to 8, characterized in that, The surface of the positive electrode active material is provided with a coating layer, which includes one or more of Li2ZrO3, LiAlO2, AlF3 and MgO, and / or the coating layer thickness is 2~20nm.

10. An electrical appliance, characterized in that, Includes the battery as described in any one of claims 1 to 9, wherein the battery serves as the power supply for the electrical device.

11. A vehicle, characterized in that, Includes the battery as described in any one of claims 1 to 9, wherein the battery serves as a power supply for the vehicle.